2019
DOI: 10.1093/ckj/sfz029
|View full text |Cite
|
Sign up to set email alerts
|

T-lymphocyte in ANCA-associated vasculitis: what do we know? A pathophysiological and therapeutic approach

Abstract: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is an autoimmune condition that commonly causes kidney impairment and can be fatal. The key participation of B-lymphocytes as ANCA producers and neutrophils as target of these antibodies is widely described as the mechanism of endothelial damage in this disease. There has been a rising interest in the role of T-lymphocytes in AAV in recent years. Evidence is strong from animal models, and T-lymphocytes can be found infiltrating kidney tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 85 publications
1
15
1
1
Order By: Relevance
“…Exhausted T cells have been shown to be increased in AAV patients. 4 Although cells expressing exhaustion markers were also increased in AAV patients compared with HCs in our study, they were not significantly different than CKD controls, suggesting that such difference is shared across individuals with kidney impairment. We did not observe significant differences in cytokine production in phorbol myristate acetate plus ionomycin-stimulated T and B cells across the 3 study groups (data not shown).…”
Section: Resultscontrasting
confidence: 58%
“…Exhausted T cells have been shown to be increased in AAV patients. 4 Although cells expressing exhaustion markers were also increased in AAV patients compared with HCs in our study, they were not significantly different than CKD controls, suggesting that such difference is shared across individuals with kidney impairment. We did not observe significant differences in cytokine production in phorbol myristate acetate plus ionomycin-stimulated T and B cells across the 3 study groups (data not shown).…”
Section: Resultscontrasting
confidence: 58%
“…Th1 cells are overexpressed in ANCA-associated vasculitis, and during acute phases of the disease, it was demonstrated that a higher Th1/Th2 ratio corresponded to higher expression of IFN-γ in the kidneys [ 130 ]. Th1 polarization is mediated in ANCA-associated vasculitis by a decrease in CD28, a costimulatory signal which promotes Th2 differentiation [ 131 ]. Th1 effector cells promote the secretion of IFN-γ and IgG3, the strongest immunoglobulin subclass in inducing neutrophil activation.…”
Section: Pathogenetic Steps In Anca-associated Vasculitis and Ancamentioning
confidence: 99%
“…23 Nonetheless, there is growing evidence of T lymphocytes' role in the pathogenesis of ANCA vasculitis, 24 25 and promoting the unopposed activity of these cells, as observed with CPI use, might explain to some degree the observed association between CPI use and renal vasculitis. [24][25][26] For example, CPIs can expand T cells (effector and follicular cells) and increase T and B cell interaction with potentially subsequent production of interferon gamma and interleukin 21-both cytokines have been previously reported to be associated with ANCA vasculitis. [27][28][29][30] CD4+ regulatory T cells (Tregs) are a highly immune-suppressive subset of CD4+ T cells and their expression of regulatory transcription factor FOXP3 is critical in maintaining self-tolerance.…”
Section: Casementioning
confidence: 99%